Inheritance of glyphosate resistance in Lolium perenne and hybrids with Lolium multiflorum. (May 2015) - Yanniccari, Marcos; Istilart, Carolina; Giménez, Daniel O.; Castro, Ana M.
Abstract: Glyphosate-resistant Lolium species have been selected in weed communities where glyphosate is the herbicide used almost exclusively for weed control. The rate of evolution of herbicide resistance is highly influenced by the mating system and the inheritance type. Given the relevance of Lolium spp. as major weeds of winter cereal crops, it is important to know the basis of how they inherit glyphosate resistance. During three years of testing, we studied Lolium perenne plants from a glyphosate-resistant population in Argentina. Plants with different glyphosate sensitivity were forced to self-fertilize and breed. In addition, inter-specific hybridizations were obtained using glyphosate-susceptible Lolium multiflorum and glyphosate-resistant L. perenne . Moderately resistant L. perenne plants, when selfed, produced offspring in three phenotype classes: susceptible, moderately resistant and highly resistant plants in a 1:2:1 ratio, respectively. When moderately glyphosate-resistant plants and susceptible ones were crossed, the offspring showed the same parental phenotypes in a 1:1 ratio. In crosses between highly resistant plants with susceptible individuals, all offspring showed moderate resistance, while crosses of susceptible plants produced 100% glyphosate-susceptible individuals. Glyphosate resistance therefore appears to be controlled by a single locus with incomplete dominance and maternal effects are unlikely to play a major role. Moreover, glyphosate resistance was inherited in hybrids between susceptible L. multiflorum and resistant L. perenne with a similar type of inheritance pattern as that indicated above. Considering these cross-pollinated species, glyphosate resistance may be transmitted not only among plants of the same species but also to related species such as L. multiflorum . Highlights: The glyphosate resistance in Lolium perenne from Argentina is controlled by a single locus with incomplete dominance. Homozygous and heterozygous genotypes exhibit resistance to normal field application rates of glyphosate. Glyphosate resistance is inherited in hybrids between susceptible L. multiflorum and glyphosate-resistant L. perenne.